A MARKETING STRATEGY ANALYSIS: MARKET ENTRY PLAN OF FLOCUS TO INDONESIAN MARKET - Valentino Nedya Kresno Aji; Harjum Muharam (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Flocus is a textile company pioneering sustainable and regenerative textile solutions based on kapok fiber, and it has been creating a responsible supply chain for kapok since 2016. By doing what they can do best such as planting kapok trees in Indonesia to cover the increasing demand and planting kapok in areas where the desertification risk is high to help the poor and delicate ecosystem to find a new balance, testing and investing the wide range of applications of kapok, and building partnership with companies to help them using kapok for a wide range of products. Since Flocus has invested in Indonesia for its supply chain, the company is thinking of entering the Indonesian market by offering its Fibers, Yarns, Fabrics, and Non-Woven products with a B2B business model in order to increase its profit. Flocus wants to expand its operations and market in Indonesia by creating a new sustainable kapok supply chain in Semarang and trying to sell its products to the locals. This expansion would be in the hope of increasing their revenue and creating a better sustainable supply chain. This study examines the enter plan to Indonesia market, including market segmentation, market size, and market growth. These studies are critical for the Flocus entrance strategy to succeed. This paper also examines cultural variations that have a large impact on marketing techniques, such as people's ideas, behaviors, and communication. The research method that the researchers will use is primary and secondary data with SWOT and PESTLE analysis. The result shows that Flocus can get into the market by selling its product in massive volume or small volume, with massive volume it means that Flocus will sell its product to another company or manufacturer, and small volume means that Flocus will sell its product more towards the consumer. The strategy to compete in Indonesian market is to target middle to big company or manufacturer, why this is a better approach than targeting small company is because there is not a lot of big textile or garment manufacturer in Indonesia, and usually in Indonesia, the small company is buying product from big company instead of creating on their own this is because the machinery in Indonesia is costly and not a lot of small company can afford it. So, targeting middle to big company is better than targeting small company.